Supercritical CO2-assisted amorphization of WO2.72 and its high-efficiency photothermal conversion. Issue 56 (12th June 2020) - Li, Youzeng; Yan, Pengfei; Guo, Cang; Xu, Qun
Abstract : Amorphization of WO2.72 was successfully achieved with the assistance of supercritical carbon dioxide (SC CO2 ). Amorphous SC CO2 -treated sample has strong optical absorbance and excellent photothermal conversion efficiency of 52.5% indicates they can be a promising photothermal agent. Abstract : Amorphous materials with unique atomic arrangements have attracted great attention owing to their unique optical and electronic properties. In this work, amorphization of pristine WO2.72 was successfully achieved with the assistance of supercritical carbon dioxide (SC CO2 ). Experimental results indicate that the obtained amorphous sample has strong optical absorbance in the near-infrared (NIR) region. Furthermore, an excellent photothermal conversion efficiency (PCE) of 52.5% indicates that it enables the capture of solar energy and converts it into thermal energy efficiently.